(untitled) (JISIPOL | Jurnal Ilmu Sosial dan Ilmu Politik, 2026)
General elections are an important instrument in realizing inclusive and equitable democracy. However, people with disabilities still often face various obstacles in exercising their voting rights, both in terms of accessibility and institutional support. This study aims to analyze the fulfillment of the political rights of persons with disabilities in the 2024 elections in Gresik Regency and to examine the role of the Indonesian Association of Persons with Disabilities in Gresik Regency (PDKGI) as a strategic partner of the General Elections Commission (KPU) in creating disability-friendly elections. This study uses a qualitative method with a case study approach through interviews, observations, and analysis of official KPU documents. The results show that the number of registered voters with disabilities reached 3,143 people, but the participation rate was still low, averaging 14.45%. This low participation rate is influenced by limited accessibility facilities at polling stations, lack of training for officers, and minimal socialization that is adaptive to the needs of persons with disabilities. The conclusion of this study emphasizes the importance of collaboration between the KPU and PDKGI in expanding outreach and increasing political awareness among persons with disabilities. The implication is that affirmative policies and increased capacity of election organizers are needed to ensure that the principle of inclusive democracy can be substantively realized at the local level.